2012
DOI: 10.1097/sla.0b013e31826b4f91
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Abdominal Aortic Aneurysm Rupture and Short-Term Mortality, 1995–2008

Abstract: Objective To examine the modern epidemiology of abdominal aortic aneurysm (AAA) rupture and short-term AAA-related mortality after the introduction of endovascular aneurysm repair (EVAR). Background Prior epidemiologic studies have demonstrated stable rates of AAA repair, repair mortality, and AAA rupture. Recently, EVAR has been introduced as a less invasive treatment method and its use has expanded to over 75% of elective AAA repairs. Methods We identified Medicare beneficiaries undergoing AAA repair and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(115 citation statements)
references
References 30 publications
(35 reference statements)
8
103
3
1
Order By: Relevance
“…6 Since the introduction of EVAR, however, overall mortality for rAAA hospitalizations with or without treatment has decreased. 1 Over the same time period, the proportion of rAAA repairs performed by EVAR has increased, while the mortality for EVAR and open repair for rAAA has decreased. If improved mortality in EVAR patients was due to selection of healthier patients, then we would expect to see an increase in mortality for patients undergoing open repair as EVAR was adopted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Since the introduction of EVAR, however, overall mortality for rAAA hospitalizations with or without treatment has decreased. 1 Over the same time period, the proportion of rAAA repairs performed by EVAR has increased, while the mortality for EVAR and open repair for rAAA has decreased. If improved mortality in EVAR patients was due to selection of healthier patients, then we would expect to see an increase in mortality for patients undergoing open repair as EVAR was adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Despite better preventive practices and increasing rates of repair of intact abdominal aortic aneurysms (AAA) in older and higher risk populations 1 , ruptured abdominal aortic aneurysm (rAAA) continues to cause over 5,000 deaths annually in the United States. 2,3 Autopsy data demonstrate that 50–70% of patients with ruptured AAA do not survive to hospital presentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Percutaneous access (pEVAR) further minimizes invasiveness compared to femoral cutdown access (cEVAR). A recently published American multicenter randomized trial with 151 patients in centers of excellence with one stent graft, reported high success rates in selected pEVAR patients when compared to cEVAR.…”
Section: Introductionmentioning
confidence: 99%
“…20 Vascular diseases, including aortic aneurysm and PAD, are increasingly prevalent in the U.S., and timely appropriate management has been shown to directly impact both mortality and major morbidity. 21,22 We limited our sample to patients whose age was between 19 and 64 years. should be concentrated among the latter group (Medicaid/uninsured).…”
Section: Data Source and Outcomesmentioning
confidence: 99%